2002
DOI: 10.1117/12.454744
|View full text |Cite
|
Sign up to set email alerts
|

<title>Multichannel vibrotactile display for sensory substitution during teleoperation</title>

Abstract: This paper presents the design and testing of a multi-channel vibrotactile display composed of cylindrical handle with four embedded vibrating elements driven by piezoelectric beams. The experimental goal of the paper is to analyze the performance of the device during a teleoperated force controlled task. As a test bed, a teleoperator system composed of two PHANToM™ haptic devices is used to trace a rectangular path while the operator attempts to maintain a constant force at the remote manipulator's tip. Four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Akamatsu et al [323] reported improvements in performance when using bimodal (audio and visual, tactile and visual) or trimodal (audio, tactile and visual) feedback, compared to visual feedback alone. Debus and 10 Vibro- Tactile Interfaces 87 others [324] showed that vibro-tactile feedback is useful for increasing user task performance (relative to visual feedback alone, vibro-tactile feedback reduced errors by 38%).…”
Section: Motivationmentioning
confidence: 97%
“…Akamatsu et al [323] reported improvements in performance when using bimodal (audio and visual, tactile and visual) or trimodal (audio, tactile and visual) feedback, compared to visual feedback alone. Debus and 10 Vibro- Tactile Interfaces 87 others [324] showed that vibro-tactile feedback is useful for increasing user task performance (relative to visual feedback alone, vibro-tactile feedback reduced errors by 38%).…”
Section: Motivationmentioning
confidence: 97%
“…In situations where other modalities provide clear information about the environment's state relative to the task (for example, clear visual feedback in the case of an assembly task), VT feedback does not seem to improve performance (Massimino, 1991;Debus et al, 2001). Common performance measures include the time to complete a task, the amount of energy required to complete it, the peak force or excess force used in carrying it out.…”
Section: Vibrotactile (Vt) Feedback In Teleoperation or Vrmentioning
confidence: 97%
“…-Dynamic physical processes, such as rolling (Yao and Hayward, 2006) or breaking. -Force magnitude and/or direction, specifically arising from contact forces (Massimino, 1991;Debus et al, 2001Debus et al, , 2002.…”
Section: Vibrotactile (Vt) Feedback In Teleoperation or Vrmentioning
confidence: 99%
“…Vibration as a representation of force may be used as an alternative to traditional force feedback when a low cost method of feedback is desired or there are concerns about impeding the operator's input [12] [7]. Though not as beneficial as traditional force feedback, this method has been validated in virtual interactions [2] and the control of hand prostheses [12]. We believe vibrotactile feedback is best for this application due to the ease of application to the control system and its ability to convey the current draw, related directly to the force exerted by the motors, without interfering with the operator's ability to control the combot.…”
Section: Introductionmentioning
confidence: 99%